A Methods engineering study on ECP Shell Crafts - Atienza, Maria Jazmin (College of Engineering, 1999)
Elvira C. Pepito Shell Crafts was established in 1989 and is engaged in the capiz handicrafts business. It manufactures lampshades, table decors, and Christmas lanterns and trimmings. The lampshades and decors produced are exported by subcontractors while the lanterns and trimmings are sold locally. Average production is 50,000 units weekly. Mr. Eustaquio Caso initially established ECP Shell Crafts. His daughter, Mrs. Elvira Pepito, inherited the company. Currently, Mrs. Pepito and her husband are the owners. Under them are one supervisor and 25 workers. Using different techniques in Methods Engineering, the group has documented ECP's systems and procedures, present layout and labor standard times. Using streamline analysis and Ishikawa diagrams, the group identified three major problems in ECP Shell Crafts. The first main problem is the poor plant layout. Different working stations are mixed up inside the plant resulting to criss crossing of flow of materials. Another problem is the lack of storage facility. Due to this, the rate of rejection of raw materials and finished goods are quite significant. Rejection rate is placed by the owners at 20 percent of total supplies. Lastly, poor housekeeping is also a problem at ECP Shell Crafts. Cleanliness and orderliness policies are not properly implemented inside the factory. Using the technique in plant designing, the group has come up with three suggested plant layouts for ECP. These layouts are evaluated using factor rating of three conditions : cost of implementation, ease of implementation and efficiency of flow of materials. To avoid rejects in the raw materials and finished products, the group suggested of making a storage facility. With this they suggested that all raw materials (capiz shells) go under quality control upon delivery by curing them with hydrochloric acid and water. The design of the storage facility is elaborated in the study. Finally the problem related to poor house keeping was evaluated by the group, and they suggested installing wastebaskets per workstation so as to minimize garbage and having a rotation within the current workers who is to be in charge of the housekeeping. Cost of wastebaskets per workstation and proper rotation of the workers is cheaper than hiring another worker to clean and be head of the maintenance of the plant. Upon generation and selection of alternatives, the group gave recommendations and steps of how it could be implemented. The secret of success of this study is the use of Methods Engineering and Work Study as a tool in solving factory problems.